Perancangan Sistem Informasi Penjualan Sepeda Motor Berbasis Web pada Showroom Arios Jaya Motor - Fernanda Jekita F. Sitepu; Rimbun Siringoriongo; Resianta Perangin-angin (Universitas Methodist Indonesia, 2024)
The Arios Jaya Motor showroom sales system currently still uses manual systems and methods, making the sales process take a long time and is inefficient. Currently, online sales systems are widely used in various showrooms, even individual companies such as Live Monza are given the opportunity to run their business. At the